LEGALIZING EUTHANASIA AND ASSISTED SUICIDE – BETWEEN FREEDOM OF CONSCIENCE, INTEGRITY AND PSEUDO-CHARITY (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Legalizing euthanasia and/or physician assisted suicide are systematically coming back on public agendas in different countries, districts or territories, based on particular experiences presented in the media. Concepts like mercy, prolonging agony, charity are being analyzed in the same manner as freedom of conscience, integrity; older concepts like love, caring and compassion are being interpreted in totally opposed ways of partisans of one approach or another. The current article is bringing into discussion the possibility or opportunity of legalizing euthanasia and/or physician assisted suicide in countries with a deeply religious background, like Romania, starting from the historical debates on the matter, and taking into account not only the patient’s perspective, but also the practitioners’, which are – most often – taken out from the table.